Non-linear filtering techniques for narrow-band interference rejection in direct sequence spread-spectrum systems - Kasparis, Takis; Georgiopoulos, Michael N.; Payne, E. (My University, 1991)
The authors concentrate on the problem of interference rejection for the cases of single and multitone jammers. They propose the use of a conditional nonlinear median filter operating in the transform domain, for the detection and suppression of narrowband signals of sufficient power, without regard to their center frequency, bandwidth, or peak power. It is shown that this approach offers several significant advantages over similar techniques that have been used for.
Keywords: Signal detection; Filters and filtration; Signal processing